Pengaruh ROA terhadap Harga Saham Dimediasi EPS pada Perusahaan Indeks MNC36 Periode 2019-2024 - Benedictus Yovandrey Wiliyus Moniung; Faradila Meirisa (MDP Student Conference, 2026)
This study aims to examine the effect of Return on Assets (ROA) on Stock Price with Earning Per Share (EPS) as a mediating variable. The research focuses on companies listed in the MNC36 Index for the period 2019-2024. Using a quantitative associative approach and purposive sampling, 30 companies were selected, totaling 180 observations. Data analysis was performed using Path Analysis and the Sobel Test via IBM SPSS 26. The results indicate that ROA has a significant positive effect on Stock Price, and EPS also significantly affects Stock Price. However, ROA does not significantly affect EPS. Furthermore, the Sobel Test reveals that EPS is unable to mediate the relationship between ROA and Stock Price. This suggests that investors respond to asset efficiency directly rather than through earnings per share mechanisms in determining stock value.